2010
DOI: 10.1080/03066150.2010.494372
|View full text |Cite
|
Sign up to set email alerts
|

A neoliberalisation of civil society? Self-help groups and the labouring class poor in rural South India

Abstract: This paper notes the prominence of self-help groups (SHGs) within current anti-poverty policy in India, and analyses the impacts of government- and NGO-backed SHGs in rural North Karnataka. It argues that self-help groups represent a partial neoliberalisation of civil society in that they address poverty through low-cost methods that do not challenge the existing distribution of power and resources between the dominant class and the labouring class poor. It finds that intra-group savings and loans and external… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 32 publications
1
51
0
Order By: Relevance
“…In a cycle of debt, the workers had to borrow from money lenders to pay back a loan amount borrowed through their self-help groups. As Pattenden (2010) points out in a similar case from the south Indian state of Karnataka, this enforcement of debt cycle upon the rural poor in effect makes the self-help groups a proxy money lender (p. 498).…”
mentioning
confidence: 92%
“…In a cycle of debt, the workers had to borrow from money lenders to pay back a loan amount borrowed through their self-help groups. As Pattenden (2010) points out in a similar case from the south Indian state of Karnataka, this enforcement of debt cycle upon the rural poor in effect makes the self-help groups a proxy money lender (p. 498).…”
mentioning
confidence: 92%
“…Pattenden (2010) supports this approach as he suggests that self-help initiatives like the one found in UMABU address poverty through low-cost methods that do not challenge the global elite or longstanding economic social relations. In the case of UMABU and other NGOs around the world, these kinds of selfhelp initiatives fit nicely within the worldview of Western development organisations.…”
Section: Umabu and Tdh Historical Contextmentioning
confidence: 81%
“…Aminur Rahman has revealed how female borrowers in Bangladesh have physically attacked small businesses developed with microcredit schemes, either out of jealousy or when women borrowers have failed to return loans on time (Rahman, 1999, p. 57-82). In southern India, three recent studies have clearly shown that caste and class relationships influence micro-credit outcomes, women from low castes and low classes being either excluded from or unable to make effective use of SHG schemes (Garikipati, 2008;Rao, 2008;Pattenden, 2010).…”
Section: Introductionmentioning
confidence: 99%